Gambaran Tatalaksana Nyeri Skala 1-3 Pada Pasien Kanker Di Ruang Perawatan Onkologi RSUP Dr. Kariadi Semarang - Mufid Mufid (Medica Hospitalia : Journal of Clinical Medicine, 2019)
Background of the Study: Cancer is a disease or abnormalities of cells that grow new abnormally, excessively, uncontrollably, and finally can attack and spread to other organs around it. The pain always impairs cancer patients, it will differentially impair cancer patients', from mild, moderate, and severe. The pains can be overcome according to their standard: mild pain with nonpharmacology as an independent area of nursing, moderate pain with non-pharmacological and pharmacological combinations, they are collaborative areas, and severe pain with pharmacology, it is commonly given with medication. Objective of the Study: Find the description of pain management scales 1-3 by nurses towards cancer patients in oncology treatment room Dr. Kariadi General Hospital Medical Center or RSUP. Dr. Kariadi Semarang Research Methodology: The design used was descriptive quantitative with cross-sectional approach, the sample size was 124 people. The sampling technique was Cluster-random sampling. The research instrument used was questionnaire sheet, while the analysis used was descriptive statistics to be displayed in the form of frequency distribution. Results of the Study: Description of the implementation of pain management scales 1-3 by nurses towards cancer patients in oncology treatment room Dr. Kariadi General Hospital Medical Center or RSUP. Dr. Kariadi Semarang quantitatively on medical records shows that the average achievement of 95.16% (Good), quantitatively in the patients shows that the average achievement of 75.8% (Poor). Conclusion: Description of the implementation of pain management scales 1-3 by nurses towards cancer patients in oncology treatment room Dr. Kariadi General Hospital Medical Center or RSUP. Dr. Kariadi Semarang generally shows fair category. Keywords: Cancer, Pain Management, Semarang Latar Belakang : Kanker adalah penyakit atau kelainan sel-sel yang tumbuh baru secara abnormal, berlebihan, tidak terkendali, serta kemudian dapat menyerang dan menyebar ke organ lain di sekitarnya. Nyeri selalu menyertai penderita kanker, dengan tingkat nyeri yang dirasakan oleh penderita bervariasi, dari ringan, sedang, dan berat.Nyeri dapat ditanggulangi sesuai standartnya: yang ringan dengan non farmakologi sebagai area independen keperawatan, sedang dengan kombinasi non farmakologi dan farmakologi yaitu area kolaboratif, dan berat dengan farmakologi biasanya dengan pemberian medikasi. Tujuan penelitian: Mengetahui gambaran tatalaksana nyeri skala 1-3 oleh perawat pada pasien kanker diruang perawatan onkologi RSUP Dr. Kariadi Semarang Metode Penelitian : Desain yang digunakan deskriptif kuantitatif dengan pendekatan cross-sectional, besar sampel 124 orang. Tehnik sampling Clusterrandom sampling. Instrumen penelitian menggunakan lembar kuesioner sedangkan analisis yang digunakan statistik diskriptif yang akan ditampilkan dalam bentuk distribusi frekuensi. Hasil Penelitian : Gambaran implementasi tatalaksana nyeri skala 1-3 oleh perawat pada pasien kanker diruang perawatan onkologi RSUP Dr. Kariadi Semarang secara kuantitatif pada rekam medis menunjukkan bahwa rata – rata capaian 95,16 % (baik), secara kuantitatif pada pasien menunjukkan bahwa rata – rata capaian 75,8 %(kurang baik). Kesimpulan : Gambaran implementasi tatalaksana nyeri skala 1-3 oleh perawat pada pasien kanker diruang perawatan onkologi RSUP Dr. Kariadi Semarang secara umum menunjukkan cukup baik. Kata kunci : Kanker , Tatalaksana nyeri, Semarang